12-19 = -7x

In this equation, x is the variable so we must solve for x:

First simplify:

-7 = -7x

Now to get x (the variable) by itself, we need to divide both sides by -7:

`-7/-7 = (-7x)/-7`

`therefore1=x`

`therefore` **x=1**

To check that this satisfies the equation, substitute x=1 into

12-19= -7x

`therefore` -7=-7 (1)

`therefore -7=-7`

**Therefore x=1 satisfies the equation**

12 -19 = -7x

We want to solve for x. First see if you can simplify either side of the equation.

Here we can. So we get:

-7 = -7x

To get x by itself, we divide by -7. This makes:

1 = x

To solve this equ, we should:

- Rewrite: 12-19= -7x
- Subtract & Simplify: -7=-7x
- Isolate the variable by dividing -7 from both sides: `(-7/-7)=(-7x)/(-7)`
- Simplify, and our answer should be
**x=1**

12 - 19 = -7x

To solve this equation , first combine the like terms . By combining the like terms , you should get

-7 = -7x now we have to try to get " x " alone . In order to get " x " alone divide by -7 on both sides

By dividing by -7 on both sides , you should get

x = -1 which is your answer

A)12-19= -7x

combine like terms

-7=-7x

divide both sides by -7

`-7/7 = (-7x)/-7`

1=x